Dormancy in peach (Prunus persica) flower buds. V. Anatomy of bud development in relation to phenological stage - Reinoso, Herminda (2002)
Anatomical changes in the peach (Prunus persica (L.) Batsch.) flower buds were defined and then assessed and correlated with the phenological stage from early dormancy through to flower opening. The peach flower bud, unlike the vegetative bud, shows a continuous anatomical development during the late autumn and winter dormancy period, even though there are no obvious macroscopic changes. Sterile whorls differentiate rapidly in late summer through early autumn. In contrast, fertile whorls develop very slowly during winter; their rapid development begins in late winter and continues through early spring. The androecium develops throughout the winter, while the gynoecium develops in late winter. By late winter, the anthers begin to undergo microsporogenesis and microgametogenesis and the ovaries have formed ovules. Vascular connections between flower primordia and branch wood are complete by late winter, when rapid phenological changes begin. At this point in time, the peach floral bud enters a “rapid maturation phase” that ends in flower opening. Thus, for the peach flower bud at least, the concept of dormancy as “a temporary suspension of visible growth of any plant structure containing a meristem” that was proposed by earlier researchers appears inappropriate. Rather, cell division, enlargement, and differentiation, which lead to organogenesis, take place throughout the entire “dormancy” period.